KH KHOIRON SYU'AIB'S DA'WAH IN SUPPORTING THE CAREER TRANSITION OF EX-COSTS IN THE EX-LOCALIZATION OF BANGUNSARI SURABAYA - Risma Azzah Fatin; Ibnu Azka (J-MD Jurnal Manajemen Dakwah, 2024)
This research aims to analyze KH Khoiron Syu'aib's da'wah strategy in supportingthe career transition of former commercial sex workers (PSK) in the formerBangunsari localization, Surabaya. The government's closure of Bangunsariprostitution localization had a significant impact on former prostitutes who losttheir livelihoods. In this context, da'wah plays an important role in providing moral,spiritual and practical support to help them transition to a more dignifiedprofession. This research uses a qualitative approach with a case study method toexplore the da'wah strategy implemented by KH Khoiron Syu'aib. Data wascollected through interviews with KH Khoiron Syu'aib, a former prostitute, andlocal community leaders. Direct observation and documentation were also carriedout to complete the data. The results of this research show that KH Khoiron Syu'aibuses a holistic and comprehensive da'wah approach, including spiritual aspects,skills development, economic empowerment and psychosocial support. Throughregular recitations, skills training and economic empowerment programs, KHKhoiron Syu'aib has succeeded in increasing the awareness and ability of formerprostitutes to switch to other, more dignified professions. Apart from that, thepsychosocial support provided also helps former prostitutes overcome social stigmaand increase their self-confidence. This research concludes that KH KhoironSyu'aib's da'wah strategy is effective in supporting the career transition of formerprostitutes in the former Bangunsari localization. A holistic and comprehensiveapproach is the key to success in changing the lives of former prostitutes andimproving their welfare. It is hoped that these findings can become a reference forsimilar empowerment programs in other regions, as well as contributing to thedevelopment of a more effective and sustainable da'wah model in overcoming thesocial and economic problems faced by former prostitutes in Indonesia.